Interdental Alveolar Distraction In an Adult Patient with a Unilateral Wide Alveolar Cleft: Case Report - Aslıhan Uzel; Mehmet Kürkçü (Galenos Yayinevi, 2010)
Aim:To demonstrate treatment of an adult patient with a wide unilateral cleft by segmental alveolar distraction using a hyrax screw.Subjects and Methods:An 18 year-old boy presented with a right complete cleft lip and palate; collapsed lateral segments; a retruded position of the premaxilla; and a Class III relationship. Tollowing orthodontic expansion and alignment of the upper teeth the residual width of the cleft was too wide to successfully grafting and it was decided to mesialize the right buccal segment surgically by means of callus distraction using an intraoral tooth-anchored hyrax screw under local anesthesia. After three weeks of activation and a 12 weeks retention period bone grafting was performed.Results:After alveolar grafting the cleft was found to have an osseous closure with adequate soft tissue coverage and the integrity of the maxilla was provided. However, as the skeletal relation was not appropriate for the space closure of the missing lateral incisor the disuse atrophy of the grafted bone could not be prevented.Conclusion:Segmental alveolar distraction can be a good choice in the treatment of adult patients with wide residual alveolar clefts. But, teeth movement is the most important factor in the long term success of the grafted bone.